Peptide Uptake Is Essential for Borrelia burgdorferi Viability and Involves Structural and Regulatory Complexity of its Oligopeptide Transporter - Ashley M. Groshong (American Society for Microbiology, 2017)
ABSTRACT Borrelia burgdorferi is an extreme amino acid (AA) auxotroph whose genome encodes few free AA transporters and an elaborate oligopeptide transport system (B. burgdorferi Opp [BbOpp]). BbOpp consists of five oligopeptide-binding proteins (OBPs), two heterodimeric permeases, and a heterodimeric nucleotide-binding domain (NBD). Homology modeling based on the crystal structure of liganded BbOppA4 revealed that each OBP likely binds a distinct range of peptides. Transcriptional analyses demonstrated that the OBPs are differentially and independently regulated whereas the permeases and NBDs are constitutively expressed. A conditional NBD mutant failed to divide in the absence of inducer and replicated in an IPTG (isopropyl-β-d-thiogalactopyranoside) concentration-dependent manner. NBD mutants grown without IPTG exhibited an elongated morphotype lacking division septa, often with flattening at the cell center due to the absence of flagellar filaments. Following cultivation in dialysis membrane chambers, NBD mutants recovered from rats not receiving IPTG also displayed an elongated morphotype. The NBD mutant was avirulent by needle inoculation, but infectivity was partially restored by oral administration of IPTG to infected mice. We conclude that peptides are a major source of AAs for B. burgdorferi both in vitro and in vivo and that peptide uptake is essential for regulation of morphogenesis, cell division, and virulence. IMPORTANCE Borrelia burgdorferi, the causative agent of Lyme disease, is an extreme amino acid (AA) auxotroph with a limited repertoire of annotated single-AA transporters. A major issue is how the spirochete meets its AA requirements as it transits between its arthropod vector and mammalian reservoir. While previous studies have confirmed that the B. burgdorferi oligopeptide transport (opp) system is capable of importing peptides, the importance of the system for viability and pathogenesis has not been established. Here, we evaluated the opp system structurally and transcriptionally to elucidate its ability to import a wide range of peptides during the spirochete’s enzootic cycle. Additionally, using a novel mutagenesis strategy to abrogate opp transporter function, we demonstrated that peptide uptake is essential for bacterial viability, morphogenesis, and infectivity. Our studies revealed a novel link between borrelial physiology and virulence and suggest that peptide uptake serves an intracellular signaling function regulating morphogenesis and division.